Analyse des ajustements réciproques dans une activité de coenseignement - Éric Saillot; Séverine Malmaison
This text presents a study about a french educational device called « Plus de maîtres que de classes » (PMQC) introduced in the context of the refoundation of the french school (2013) to improve the skills of pupils in difficulties. This educational reform aims to provide an additional teacher in a school to allow new educational organizations, especially co-teaching that share that share teaching activities. Mainly based on the researchs carried out by Bucheton (2009) about adjustements skills in teaching and professional posture of scaffolding (Bucheton et Soulé, 2009, Saillot, 2015), our scientific issue aims to caraterize co-teaching when both teachers are fitting each other. We will try to understand how they both fit each other in order to improve coteaching.